2018
DOI: 10.14814/phy2.13805
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-heat stress with and without water replacement alters brain structures and impairs visuomotor performance

Abstract: Effects of exercise‐heat stress with and without water replacement on brain structure and visuomotor performance were examined. Thirteen healthy adults (23.6 ± 4.2 years) completed counterbalanced 150 min trials of exercise‐heat stress (45°C, 15% RH) with water replacement (EHS) or without (~3% body mass loss; EHS‐DEH) compared to seated rest (CON). Anatomical scans and fMRI Blood‐Oxygen‐Level‐Dependent responses during a visuomotor pacing task were evaluated. Accuracy decreased (P < 0.05) despite water replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 80 publications
0
35
0
1
Order By: Relevance
“…This is a general issue in studies with volunteering participants and there is a general underrepresentation of investigations involving females in heat-studies. However, impaired motor-cognitive performance has been reported in both those including both women and men 7,[47][48][49][50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…This is a general issue in studies with volunteering participants and there is a general underrepresentation of investigations involving females in heat-studies. However, impaired motor-cognitive performance has been reported in both those including both women and men 7,[47][48][49][50][51][52] .…”
Section: Discussionmentioning
confidence: 99%
“…One study showed that the brain volume significantly increased after 1.5 L water consumption, compared to dehydration induced by water restriction for 16 h, among 12 healthy adults [62]. Further, a randomized controlled trial of 13 young adults, investigating the effects of exercise heat stress with and without water supplementation on brain structure and cognitive performance, reported that the brain ventricles decreased and periventricular structures, such as the cerebellum, increased after water replacement compared to dehydration [20]. Another study reported that dehydration and rehydration did not affect brain volume [63].…”
Section: Discussionmentioning
confidence: 99%
“…The early reductions in CBF seen during strenuous exercise in the heat, with and without dehydration, have been postulated to reduce cerebral oxygenation [ 115 ]. A lower vascular and neuronal oxygenation could potentially compromise the cerebral metabolic rate for oxygen (CMRO 2 ), thereby contributing to the overall process of fatigue [ 115 ], reductions in motor output [ 116 , 117 ] and reductions in cognitive performance [ 118 121 ] that are magnified in hot environments and/or when dehydrated [ 118 , 122 124 ]. The characterisation of the CMRO 2 dynamics during exhaustive exercise is therefore a key question in integrative human physiology.…”
Section: Heat Hydration and The Brainmentioning
confidence: 99%